A high cerebrospinal fluid soluble TREM2 level is associated with slow clinical progression of Alzheimer's disease. Issue 1 (7th December 2020) - Edwin, Trine Holt; Henjum, Kristi; Nilsson, Lars N.G.; Watne, Leiv Otto; Persson, Karin; Eldholm, Rannveig Sakshaug; Saltvedt, Ingvild; Halaas, Nathalie Bodd; Selbæk, Geir; Engedal, Knut; Strand, Bjørn Heine; Knapskog, Anne‐Brita
Abstract: Introduction: The progression rate of Alzheimer's disease (AD) varies and might be affected by the triggering receptor expressed on myeloid cells (TREM2) activity. We explored if cerebrospinal fluid (CSF) soluble TREM2 (sTREM2), a proxy of microglial activity, is associated with clinical progression rate. Methods: Patients with clinical AD (N = 231) were followed for up to 3 years after diagnosis. Cognitively healthy controls (N = 42) were followed for 5 years. CSF sTREM2 was analyzed by enzyme‐linked immunosorbent assay. Group‐based trajectory modeling revealed distinct clinical progression groups. Results: Higher CSF sTREM2 was associated with slow clinical progression. The slow‐ and medium‐progressing groups had higher CSF sTREM2 than the cognitively healthy, who had a similar level to patients with rapid clinical progression. Discussion: CSF sTREM2 levels were associated with clinical progression in AD, regardless of core biomarkers. This could be useful in assessing disease development in relation to patient care and clinical trial recruitment.